Interpretation And Application Of The New York Convention In Turkey - Özsunay, Ergun (Springer International Publishing, 2017)
Despite some difficulties in its application, the New York Convention is still the most successful convention in Turkish arbitration practice. This chapter, while indicating the principal problems and controversies surrounding the application of the New York Convention in light of judicial precedents, also provides a picture regarding its implementation in Turkey and the ongoing developments on Turkey’s way to becoming an arbitration-friendly country.
Keywords: New York Convention